Adiksi Smartphone dan Faktor-Faktor yang Memengaruhinya pada Penumpang Transjakarta - Prayogi Miura; Elisabeth Rukmini (Jurnal Perkotaan, 2016)
Transjakarta passenger is one of the potraits of urban society that use smartphone in DKI Jakarta. Excessive use of smartphones can cause addiction for the users. This study intended to determine the prevalence of smartphone addiction of the Transjakarta passengers and the relationship of smartphone addiction related to risk factors, such as age, gender, educational status, job, and the common use of smartphones. This study used cross sectional multivariate analytical studies with the logistic regression of a total of 143 respondents selected by consecutive sampling at ten stations of Transjakarta. Fifty persons were asked to fill out the Smartphone Addiction Scale (SAS) questionnaire. The majority of the sample were female (65%), aged of 21-25 years (53%), high school graduates (88%), working as employees (81%) and doing frequent communication daring (64%). Prevalence of Transjakarta passengers who were addicted to smartphones were 68%. Risk factors of smartphone additiction, including: gender, age, educational background, job, and the common use of smartphones did not significantly related to the status of smartphone addiction.Results of the logistic regression test showed that there was no significant relationship between smartphone addiction related to risk factors. But the high percentage of respondents who were addicted to smartphone should be taken into consideration for the prevention of smartphone addiction.